PERCERAIAN DAN AKIBATNYA MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Agnes Maria Janni Widyawati (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2020)
The purpose of marriage according to Law No.1 of 1974 is to form a happy and eternal family based on The One Almighty God, but in reality not all marriages go as expected, often marriages have to run aground in the middle of the road due to conflicts between a married couple who cannot be resolved except with a judge's decision on the demands of one of the parties in the marriage. The occurrence of divorce has consequences for husband and wife, namely after the marriage breaks up due to divorce, the husband and wife are free to remarry, provided that the ex-wife must pay attention to the waiting time. Besides, it will have consequences on the relationship between husband and wife, children and on property in marriage.